Curie depth estimated from high‑resolution aeromagnetic data of parts of lower and middle Benue trough (Nigeria) - Abdullahi, Mukaila; Kumar, Raj (My University, 2020)
To quantitatively understand the geodynamic process of a region, study of geothermal parameters underneath the earth surface is very paramount. Curie depth can be an alternative to delineate geothermal parameters. In the present study, we estimated Curie depthsfrom the power spectra of 25 equally window sizes areas/points with 50% overlap extracted from high-resolution aeromagnetic anomalies of parts of lower and middle Benue Trough, Nigeria using modifed centroid method based on fractal distribution of magnetic sources.Curie depths with associated uncertainties calculated from the region under study are between 11±2 and 27±2 km. The shallowest depth (11±2) km is calculated around the area of Abakaliki whereas the deepest depth is calculated around Otukpa area of Anambra basin. The shallowest Curie depth as calculated is related with the Abakaliki anticlinorium while the deepest result is in connection with the Anambra basin. These suggest that different geological structures and magnetic anomalies (i.e. high or low magnetic anomaly) infuenced the calculated Curie depth results. In the region, it is noted that lower Curie depths (14–18 km) are recorded over the basement rocks and Curie depths between 18 and 22 km within zones of volcanoes. The interpretation hypothesized presence of underplating in the crust and possibly mantle plume as a result of the Mesozoic–Cenozoic volcanic magmatism (magmatic centers) mostly basalts distributed and scattered in the region. It has also been hypothesized that the uncertainties calculated (±0.2 to±5.0) in the region correlate more strongly with the geology, tectonic structures and type of anomalies than estimated Curie depths.
Keywords: Geothermal; Curie depth; High-resolution aeromagnetic data; Modifed centroid method; Benue trough (Nigeria)